2011
DOI: 10.1177/0958928711401769
|View full text |Cite
|
Sign up to set email alerts
|

Individual policy preferences for vocational versus academic education: Microlevel evidence for the case of Switzerland

Abstract: MPIfG Discussion Papers are refereed scholarly papers of the kind that are publishable in a peer-reviewed disciplinary journal. Their objective is to contribute to the cumulative improvement of theoretical knowledge. The papers can be ordered from the institute for a small fee (hard copies) or downloaded free of charge (PDF). AbstractThis paper uses an original dataset from a survey conducted in Switzerland in 2007 to explore the dynamics of education policy preferences. This issue has largely been neglected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Initial evidence from the micro level reinforces the notion that support for educational expansion is associated with partisan ideologies. Relying on survey data from Switzerland, Busemeyer, Cattaneo and Wolter (2011) show that individuals who identify with the political left are significantly more likely to support public spending on education and oppose tuition fees for higher education. Ansell (2010: 134) and Busemeyer (2010), using the ISSP data, also find that partisan supporters of the left are more likely to be in favour of increases in public education spending, independent of their individual socio-economic backgrounds.…”
Section: The Partisan Politics Of Educational Expansionmentioning
confidence: 99%
“…Initial evidence from the micro level reinforces the notion that support for educational expansion is associated with partisan ideologies. Relying on survey data from Switzerland, Busemeyer, Cattaneo and Wolter (2011) show that individuals who identify with the political left are significantly more likely to support public spending on education and oppose tuition fees for higher education. Ansell (2010: 134) and Busemeyer (2010), using the ISSP data, also find that partisan supporters of the left are more likely to be in favour of increases in public education spending, independent of their individual socio-economic backgrounds.…”
Section: The Partisan Politics Of Educational Expansionmentioning
confidence: 99%
“…As Busemeyer et al (2011) showed for the case of Switzerland, individuals tend to support additional spending on those sectors of the education system with which they have individual experiences. This can be conceived of as a 'socializing effect'.…”
Section: Literature Review and Theorymentioning
confidence: 99%
“…Yet, when it comes to preferences for different kinds of education policy -the focus of this article -international survey data contain no information. Hence, Busemeyer et al (2011) used data from a survey conducted in Switzerland to study this issue.…”
Section: Literature Review and Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, while large firms are more likely to support state investment in general education rather than VET, smaller firms are expected to promote more public investment in VET due to their disadvantages in organising firm-level training (Culpepper, 2003). Similarly, labour market outsiders, who are mostly in insecure employment, are not covered in social protection systems or represented by labour unions, will prefer public investment in initial-VET more than the insiders as it improves the opportunities of these individuals to get better and more secure jobs (Boix, 1998;Estevez-Abe et al, 2001;Iversen and Stephens, 2008;Busemeyer et al, 2011;Busemeyer, 2015c). In the end, VET systems supported by outsiders will have different partisan politics and characteristics from the VET systems shaped by the insiders.…”
Section: The Political Economy and Structure Of Vet Systemsmentioning
confidence: 99%